Elevated N-Terminal Pro-B-Type Natriuretic Peptide (Nt-Probnp) Levels in Critically Ill Patients with Normal Transthoracic Echocardiogram and Normal Renal Function Tests - Dar, Kamran Mahmood; Saleem, Zulqarnain; Hussain, Kamil; Malik, Abbas; Khan , Asad Zaman (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine frequency of critically ill patients who have elevated N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels with normal transthoracic echocardiogram and normal renal function tests. Study Design: Descriptive cross-sectional study. Place and Duration of Study: Medical Intensive Care Unit (ICU) of Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Jul 2022 Methodology: All patients fulfilling inclusion criteria and admitted in ICU of PEMH over the duration of study were enrolled in the study through non-probability consecutive sampling. Data for 50 patients was collected and their NT-proBNP levels in pg/mL were measured at admission and compared with reference limit based on age, for excluding congestive heart failure (CHF) after which frequency and percentage of patients with elevated NT-proBNP levels was calculated. Results: Majority of critically ill patients with normal transthoracic echocardiogram and normal renal function tests had elevated NT-proBNP levels. Out of 50 patients included in this study, 37(74 %) had elevated NT-proBNP levels. Conclusion: At the time of admission in ICU, critically ill patients with normal transthoracic echocardiogram and normal renal function tests had markedly elevated NT-proBNP levels. Thus, NT-proBNP levels alone cannot be reliably used in critically ill patients to rule out heart failure.